2004
DOI: 10.1136/jcp.2003.014274
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of giant hairy naevi

Abstract: Background: Congenital neomelanocytic naevi appear in nearly 1% of newborns. Giant hairy naevi (GHN) are uncommon lesions covering large areas of the body. They are of concern because they have the potential to transform into malignant melanomas. Aims: To describe gene expression profiles of GHN and nearby normal skin from patients with GHN and normal control skin (from patients with cleft lip/palate). Methods: Tissues from three patients with GHN and two normal controls were studied for differences in gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…43,45,55,95-99 Changes in gene regulation associated with deoxyribonucleic acid repair mechanisms or tumor resistance to chemotherapy were observed in giant congenital melanocytic lesions. 98 Furthermore, evidence has shown the importance of structural chromosomal abnormalities in the process of malignant transformation of these lesions.…”
Section: Evolutionmentioning
confidence: 99%
“…43,45,55,95-99 Changes in gene regulation associated with deoxyribonucleic acid repair mechanisms or tumor resistance to chemotherapy were observed in giant congenital melanocytic lesions. 98 Furthermore, evidence has shown the importance of structural chromosomal abnormalities in the process of malignant transformation of these lesions.…”
Section: Evolutionmentioning
confidence: 99%
“…Some of these melanoma simulators, such as proliferative nodules, may be composed of immature, benign melanocytes (20–23). Although not routine, recent investigational studies are being undertaken to determine whether the presence of genomic aberrations can be used to distinguish among MM, benign CMN, and melanoma simulators (24,25,34). One study showed a clear distinction in the number of gross chromosomal aberrations between MM and CMN.…”
Section: Absolute Indications For Treatmentmentioning
confidence: 99%
“…Several groups have studied gene expression profiles in skin tumors [18][19][20]. Others have used global profiling to examine differences between normal and altered skin, such as samples from giant nevi (moles) [21] or keloids (scar-tissue-like benign tumors) [22]. Bernard et al [23] examined human skin treated with different topical retinoids and discovered new insights into the complex activity of retinoids on keratinocytes.…”
Section: Global Transcriptional Profiling Of Skin Biopsies To Discovementioning
confidence: 98%